PENGARUH EDUKASI TENTANG KESEHATAN REPRODUKSI TERHADAP TINGKAT PENGETAHUAN REMAJA KELAS X DI SEKOLAH MENENGAH KEJURUAN SARASWATI 1 DENPASAR - Rangkoratat, Sherly Yulyan; Simatupang, Lenny Lusia (STIKes Mitra Husada Medan, 2024)
The effect of education about reproductive health on the level of knowledge of adolescents at Saraswati 1 Denpasar Vocational High School from the results of the Wilcoxon signed test obtained an asymp sig. (2-tailed) value of 0.000 smaller than the alpha level of 5% (0.05) so that it rejects ho, and it can be concluded that there is an influence between the pre-test and post-test on reproductive health education with a value of (0.000).